2016
DOI: 10.1093/carcin/bgw007
|View full text |Cite
|
Sign up to set email alerts
|

Low doses of gamma irradiation potentially modifies immunosuppressive tumor microenvironment by retuning tumor-associated macrophages: lesson from insulinoma

Abstract: Tumor infiltrating iNOS+ macrophages under the influence of immunosuppressive tumor microenvironment gets polarized to tumor-promoting and immunosuppressive macrophages, known as tumor-associated macrophages (TAM). Their recruitment and increased density in the plethora of tumors has been associated with poor prognosis in cancer patients. Therefore, retuning of TAM to M1 phenotype would be a key for effective immunotherapy. Radiotherapy has been a potential non-invasive strategy to improve cancer immunotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
77
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 39 publications
8
77
1
Order By: Relevance
“…However, there were also studies showing that radiation therapy could redirect TAMs from protumorigenic to antitumoral cells. For example, low-dose (2 Gy) whole-body irradiation induced iNOS expression and the production of proinflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), IL-12 (p70), and IFN-γ in peritoneal macrophages and TAMs (120). A recent study on murine insulinoma demonstrated that low-dose (2 Gy) irradiation induced iNOS expression in macrophages both in vitro and in vivo .…”
Section: The Tumor Microenvironment Irradiation Dictates Antitumor Inmentioning
confidence: 99%
“…However, there were also studies showing that radiation therapy could redirect TAMs from protumorigenic to antitumoral cells. For example, low-dose (2 Gy) whole-body irradiation induced iNOS expression and the production of proinflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), IL-12 (p70), and IFN-γ in peritoneal macrophages and TAMs (120). A recent study on murine insulinoma demonstrated that low-dose (2 Gy) irradiation induced iNOS expression in macrophages both in vitro and in vivo .…”
Section: The Tumor Microenvironment Irradiation Dictates Antitumor Inmentioning
confidence: 99%
“…For this point of view, M1 effector phenotype of macrophage thus represent the most suitable target cell populations for rendering tumor directed therapeutic interventions more effective. Histo-pathological analysis of several tumors revealed that around 50% of the tumor mass is composed of leukocyte among which T-lymphocytes and macrophages represent the major proportion Figure 1, thus reflecting the signals from the microenvironment they dwell in [90,91]. Classically activated macrophages are immunostimulatory with Th1-orienting properties while M2 are immunoregulatory with Th2 immune response [92].…”
Section: Macrophage-directed Cancer Immunotherapymentioning
confidence: 99%
“…Classically activated macrophages are immunostimulatory with Th1-orienting properties while M2 are immunoregulatory with Th2 immune response [92]. Tumor polarized macrophages are referred as tumor-associated macrophage (TAM) [93,94], which exhibits several pro-tumoral functions, mentioned above [90,95]. TAM accumulation in majority of tumours and subsequent phenomenal changes being a major hurdle resulting in poor cancer prognosis, macrophage depletion, e.g.…”
Section: Macrophage-directed Cancer Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations